ANALISIS PERAN HUMAS PEMERINTAH DAERAH PROVINSI BENGKULU DALAM MENJALANKAN HUBUNGAN DENGAN PERS (Studi pada Dinas Perhubungan, Komunikasi dan Informatika Provinsi Bengkulu) - Yetti Herawati; Linda Astuti; Maryaningsih - (UNIVED PRESS, Universitas Dehasen Bengkulu, 2014)
Government Public Relations could serve as a means or channel of government agencies in running relationship with the press, including the Local Government of Bengkulu province. This study aimed to see at how public relations play this role. The method used in this research was descriptive qualitative method in which the data collection was conducted by semi- structured interviews to research subjects. It’s possible for researchers to develop questions appropriate to the situation and condition so it was possible to get complete data. From the research, the role of PR in the Bengkulu Provincial Government ran good relationship with the press. The good role of the public relations could be demonstrated by the implementation of most of the series of activities such as: building and maintaining a good relationship with the press, served and understood the media, press interviews, broadcast rebuttal, filling out the important public section in the press, and documentation.Keywords : Public Relation Role, Mass Media Relation